Covid-19 or the endemic vulnerability of unequal and polarized urban spaces? The case of Lisbon Metropolitan Area - Santos, S.; Ferreiro, Maria de Fátima (AMPS architecture, media, politics, society, 2021)
Economic globalization didn’t delivered the flat map where everything is equalized. On the contrary Covid-19 has exposed and explored the profound inequalities and polarizations that have settled in society and territories. These can be detected at different scales: between the Global North and Global South, between countries, between regions or within urban areas such as Lisbon Metropolitan Area (LMA). Socio-spatial differentiation patterns and environmental degradation - expressions of a global market economy oriented to growth and competitiveness are now traduced in a set of vulnerabilities uncovered by the pandemic crisis. Contrasts were made visible between the more qualified classes and the less qualified classes, more exposed to infection and unemployment due to its precarious housing conditions and reliance on fragile or informal employment contracts. At the macroeconomic level the pandemic revealed the risks of territorial specialization. Major economic losses were observed in the gentrified centers excessively reliant on tourism. Also the possible disruption of global value production chains brought to light problems related to deindustrialization and rural abandonment and the need to enforce short supply chains in order to increase territorial resilience to external unpredicted shocks. Finally at the environmental level new concerns were raised about the retroactive impacts of urbanization on ecosystems loss. Having this in mind the paper has the following goals: I) the mapping of social-economic and environmental polarization in the case of Lisbon Metropolitan Area II) to explore the existent link between increased urban inequality/polarization and increased urban vulnerability to extreme scenarios such as covid-19 global pandemic III) to conclude on the need to detach public polices and planning practices from market logics and to consider them as key recovery instruments for a more inclusive, diverse and sustainable urban future.